Composite structures in tension, compression, and shearing - Chew, Javier Meng Ghim (2014)
Composites are increasingly being used in primary aircraft structures such as aerospace stiffeners shaped like an I-beam. Stiffeners could be found in aircraft wings to transfer bending loads onto the ribs and spars. While research has been done regarding the effect of bending loads on composite structures, there is limited research on the fabrication, failure modes in bending and crack propagation of carbon fiber composite I-beams. The objective of this project is to investigate into the effect of bending loads on carbon fiber I-beam composite structures. L-930 flame retardant woven carbon-epoxy prepregs were used to fabricate the I-beams with the help of aluminum molds and autoclave curing. A step-by-step guide to fabricate the specimens was provided. Subsequently, static tests were done at an initial speed of 0.5mm/min to obtain the average static peak load so as to determine stress ratio values for the fatigue tests. Fatigue tests at a loading frequency of 5Hz and load ratio of 0.05 were also done. All tests were conducted using the MTS‐810. Static results showed that there was no rapid brittle failure as load drops till a range of 1900N to 2300N before a gradual decline till failure. Shearing displacement also makes up about 78.5% of the total actuator displacement while video analysis showed static failure modes were namely local indentation, local buckling at the top of the web, crack propagation in the web and flanges, twist and warp in the web and flanges, shear and compressive stress concentrations by the support-rollers. Shape instability was observed to contribute to earlier fatigue failure in all the specimens. In addition, fatigue failure was noticed to occur when actuator displacement, degraded stiffness changes rapidly and when degraded stiffness falls below 0.6 for all specimens. The L-930 I-beam specimens have stress concentrations caused by shear and compression instead of tension in both the bending static and fatigue tests. Future studies could research on different material paddings to be placed on support rollers to minimize the stress concentrations points.